2018
DOI: 10.5935/abc.20180252
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Vibration Training Increases Myocardial Salvage Against Acute Ischemia in Adult Male Rats

Abstract: BackgroundWhole body vibration training (WBV) is a new training program, which is safe and effective. It can be followed by the public. However, data on the safety and efficacy of vibration on myocardial ischemia reperfusion (IR) injury are lacking.ObjectiveTo examine the effect of WBV on the tolerance of the myocardium to acute IR injury in an experimental rat model.MethodsTwenty-four male Wistar rats were divided into control and vibration groups. Vibration training consisted of vertical sinusoidal whole bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
(40 reference statements)
1
8
0
1
Order By: Relevance
“…Exercise training has been proven to be an effective strategy of rehabilitation for MI patients [11,12]. Some studies detected the cardioprotective effects of different types of exercise models [6,7,9,10]. In this study, we confirmed that AET, RET, WBV, and ES enhanced the cardiac function of normal mice.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Exercise training has been proven to be an effective strategy of rehabilitation for MI patients [11,12]. Some studies detected the cardioprotective effects of different types of exercise models [6,7,9,10]. In this study, we confirmed that AET, RET, WBV, and ES enhanced the cardiac function of normal mice.…”
Section: Discussionsupporting
confidence: 78%
“…Ameliorating cardiac fibrosis and inhibiting cardiomyocytes apoptosis would be key therapeutic targets to improve cardiac function following MI. Increasing data from clinic and animal research suggests that exercise training is an effective strategy in improving cardiac function [6][7][8][9][10][11][12]. Exercise training has beneficial effects on preventing or reversing pathological cardiac remodeling by reducing collagen production [13].…”
Section: Introductionmentioning
confidence: 99%
“…From the therapeutic point of view the possible implications of PE, can contribute to improve the treatment of cardiovascular diseases, it has been reported that in a training protocol with vibration, increases cardiac tolerance to reperfusion injury after ischemia, decreases the size of the infarction and cardiac arrhythmias and facilitates spontaneous defibrillation [15]. These data suggest that exercise helps to regulate the participation of the electrical conduction system after a cardiac insult, the mechanisms by which this happens has not yet been elucidated.…”
Section: About the Cardiovascular Systemmentioning
confidence: 99%
“…5 Mesmo atividades consideradas passivas, como a vibração de corpo inteiro, tiveram efeitos benéficos em ratos, como o aumento da tolerância à isquemia miocárdica. 6 O conjunto dos resultados contribui para o entendimento dos mecanismos pelos quais o exercício tem efeitos benéficos na prevenção e no tratamento das doenças cardiovasculares.…”
unclassified